Հայաստանի Պատմության թանգարանի Լոռվա կարպետահյուս մկրատամանների հավաքածուն - Պետրոսյան, Հասմիկ (Հայաստանի պատմության թանգարան)
In the museum fund of the Republic of Armenia there are few examples of cases of scissors provided for shearing wool, containers for weavers’ scissors. According to the materials known to date, the main regions of use of these items were Lori, Syunik and Artsakh. The collection of ethnographic fabrics of the Historical Museum of Armenia was replenished with carpet scissors in 1934–35 as a result of scientific expeditions led by Stepan Lisitsyan (Lori). The aforementioned regions have centuries-old traditions of processing and weaving wool yarn. The phenomenon manifests itself in a variety of woven products, which justifies the choice of the material of homemade shears for shearing sheep, which is due to both its presence and the assessment of its properties. Considering the products in the general group of carpet weaving items, their technical forms with a complex design, a variety of forms of decorations, and the forms of weaving of woven sections are indicated. В музейном фонде РА примеры предусмотренных для острига шерсти футляров ножниц, тар для ножниц ткачей немногочислены. По известным до настоящего времени материалам, основными регионами пользования этих предметов были Лори, Сюник и Арцах. Коллекция этнографических тканей Исторического музея Армении пополнилась ковровыми ножницами в 1934-35 годах в результате научных экспедиций под руководством Степана Лисицяна (Лори). Вышеупомянутые регионы имеют многовековые традиции обработки и ткачества шерстяной пряжи. Феномен проявляется в разнообразии тканых изделий, что оправдывает выбор материала самодельных ножниц для стрижки овец, который обусловлен как его наличием, так и оценкой его свойств. Рассматривая изделия в общей группе предметов ковроделия, указаны их технические формы со сложной конструкцией, многообразием форм украшений, формами плетения тканных участков.
Keywords: Ազգագրություն